Linear Model-Based Error Identification and Calibration for Data Converters - Wegener, Carsten; Kennedy, Michael Peter (Design, Automation, and Test in Europe: Proceedings of the conference on Design, Automation and Test in Europe - Volume 1; 03-07 Mar. 2003, 2003)
For the example of a 12-bit Nyquist-rate ADC, a model for nonlinearity-causing mechanisms is developed based on circuit simulations. The model is used to estimate circuit element values from measured device characteristics. Post-manufacture reconfiguration of the digital control part of the device-type that is used as a test vehicle in this work can improve the linearity performance of a device. An algorithm is proposed that searches for a locally-optimal reconfiguration based on the determined circuit element values. Applying calibration to the circuit simulation model allows one to estimate the performance improvement obtainable with the proposed calibration scheme for a given manufacturing process prior to a physical implementation.